Bleeding Time in Rats: A Comparison of Different Experimental Conditions - Dejana, Elisabetta; Villa, Silvia; de Gaetano, Giovanni (Thrombosis and Haemostasis, 1982)
The tail bleeding time (BT) in rats definitely varies according to the method applied. Of the various variables that may influence BT, we have evaluated the position (horizontal or vertical) of the tail, the environment (air or saline), the temperature (4°, 23° or 37° C) and the type of anaesthesia. Transection of the tail tip cannot be used to screen drugs active on platelet function since it is sensitive to coagulation defects. Template BT in contrast is not modified by heparin and is sensitive to defects of platelet number and function (“storage pool disease”, dipyridamole-like drugs, exogenous prostacyclin). In contrast the test fails to detect aspirin-induced platelet dysfunction. The evidence reported indicates that thromboxane A2-prostacyclin balance is not a factor regulating BT. Aspirin treatment however may be a precipitating factor when associated with other abnormalities of platelet function.Template BT is a valid screening test for platelet disorders and for antiplatelet drugs.
Keywords: Bleeding time; Aspirin; Platelet function inhibitors; Thrombocytopenia; Drug interactions